Knowledge, attitude and practice of municipal solid waste management among highland residents in Northern Thailand - Pussadee Laor; Yanasinee Suma; Vivat Keawdounglek; Anuttara Hongtong; Tawatchai Apidechkul; Nittaya Pasukphun (College of Public Health Sciences, Chulalongkorn University, 2018)
Purpose - Chiang Rai is the northernmost province of Thailand. Municipal solid wastes (MSWs) was generated 430,828.2 ton/y in this area; however, only 24 percent of waste was properly disposed, and 43 percent of waste was properly managed. The purpose of this paper is to explore knowledge, attitudes and practices (KAP) of highland residents in order to provide a basis for the development of waste management in the study area. Design/methodology/approach - A cross-sectional study was conducted in Mae Fah Luang district, Thailand, from November 2016 to January 2017. A random sample of 451 respondents constituted the study population. Data were gathered using a structured questionnaire. Pearson Correlation and χ2 were applied to identify the association among variables. Findings - Overall, 73 percent of respondents had high level of knowledge; 85 percent of respondents showed neutral attitude; and 59 percent of respondents performed moderate practice on MSW management. The results highlighted that age and education levels were statistically significant associated with KAP levels on MSW management at (p=0.05). Originality/value - The respondents who have good knowledge also have a good level of practice; and those who have good attitude also have a good level of practice. Socio-demographic factors and suitable way to promote an effective MSW management should be considered.